Sosialisasi Pendidikan Konservatif Sejak Dini Bagi Siswa/Siswi SD Moria Kota Sorong Oleh Mahasiswa Program Studi Sistem Informasi IIb, Fakultas Ilmu Komputer, Universitas Victory Sorong - Natasya Virginia Leuwol; Deny Steward Saimima; Muh.Jamaludin Akbar; Aprilia Jeniffer Maail (CV. ITTC INDONESIA, 2024)
The problem of Moria Elementary School in Sorong, Regency has never provided knowledge about the introduction of forests and the environment to students. Knowledge of the environment and forests from an early age is an important thing to increase and conserve biodiversity to create a better life for the next generation. The aim of this activity is to foster the values, attitudes, and spirit of conservation in students through the introduction of forest and the environment activity. The introduction of forest and the environment are carried out through two activities, such as socialization activities and Discussion. Socialization activities carried out such as delivering information about the importance of reforestation, awareness of waste, and loving wildlife. The result of this activity is an increase in students’ enthusiasm and motivation to learn. During the activity, students of Moria Elementary School looked very enthusiastic. This is because learning activities are interspersed with ladder learning media. Through the educational, students can learn and repeat materials related to the introduction of forest and the environment that have been delivered by the PKM team so that this activity is expected to not only make students understand the importance of the existence of forest and the environment but also to change students’ attitude and mindset about the importance of forest and the environment for the next generation.